2012
DOI: 10.1016/j.jacc.2012.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Comparisons of New Oral Anticoagulant Drugs for Efficacy and Safety When Used for Stroke Prevention in Atrial Fibrillation

Abstract: Notwithstanding the limitations of an indirect comparison study, we found no profound significant differences in efficacy between apixaban and dabigatran etexilate (both doses) or rivaroxaban. Dabigatran 150 mg BID was superior to rivaroxaban for some efficacy endpoints, whereas major bleeding was significantly lower with dabigatran 110 mg BID or apixaban. Only a head-to-head direct comparison of the different new OACs would fully answer the question of efficacy/safety differences between the new drugs for str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
177
2
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(210 citation statements)
references
References 21 publications
15
177
2
16
Order By: Relevance
“…An indirect comparison analysis of dabigatran (2 doses), apixaban and rivaroxaban for their relative efficacy and safety against each other did not find profound differences in efficacy between them, although dabigatran 150 mg BID was superior to rivaroxaban for some efficacy endpoints (such as a composite of stroke and systemic embolism), whereas major bleeding was significantly lower with dabigatran 110 mg or apixaban [80]. Future studies may eventually confirm or refute these preliminary findings.…”
Section: Falls and Bleeding Riskmentioning
confidence: 85%
“…An indirect comparison analysis of dabigatran (2 doses), apixaban and rivaroxaban for their relative efficacy and safety against each other did not find profound differences in efficacy between them, although dabigatran 150 mg BID was superior to rivaroxaban for some efficacy endpoints (such as a composite of stroke and systemic embolism), whereas major bleeding was significantly lower with dabigatran 110 mg or apixaban [80]. Future studies may eventually confirm or refute these preliminary findings.…”
Section: Falls and Bleeding Riskmentioning
confidence: 85%
“…В то же время, медицинское сообщество выглядит довольно растерянным, когда за-дается вопросом: какой из НПА лучше? В отсутствие возможности получить результаты исследований с пря-мым сравнением данных препаратов (пожалуй, за ис-ключением данных регистров, но их интерпретацию также следует проводить с осторожностью), мы можем оперировать только статистическими выкладками в ре-зультате непрямых сравнений [6]. Не всегда такой под-ход можно признать адекватным хотя бы потому, что в вышеупомянутые исследования включались паци-енты с различным сердечно-сосудистым риском, трактовка конечных точек также была неодинако-вой.…”
Section: новые пероральные антикоагулянтыunclassified
“…Indirect comparative studies mostly reported no profound significant difference in efficacy between these three NOACs, and apixaban was consistently found to be associated with significantly less major bleeding than dabigatran (150 mg twice daily) and rivaroxaban. [7][8][9] Warfarin underuse is common due to the complexity of anticoagulation care. Warfarin therapy with good INR control (patient-time in therapeutic range (TTR) > 75 %) is associated with lower event rates when compared to poor INR control (TTR<60 %).…”
Section: Introductionmentioning
confidence: 99%